Postoperative Acute Ischemic Spinal Cord Infarction without Vertebral Fracture in Children - Poyrazoglu, Hatice Gamze; Serhatlioglu, Faruk; Per, Huseyin; Yikilmaz, Ali; Canpolat, Mehmet; Ozmen, Rifat; Kumandas, Sefer (Aves, 2016)
Anterior spinal artery infarction is extremely rare in children; it is caused by the hypoperfusion of the anterior spinal artery, leading to ischemia. Patients typically present with acute paraparesis or quadriparesis, depending on the level of spinal cord involvement. In general, it is clinically diagnosed, and neuroimaging is used to confirm the diagnosis and exclude other conditions. There are only a few reports in the pediatric literature characterizing the etiology, diagnosis, treatment, and prognosis of spinal cord infarction. It is associated with moderate-to-severe disabilities and a high mortality rate. Here we report an unusual case wherein a 12-month-old male developed spinal cord infarction following surgery to repair the coarctation of the aorta. Spinal magnetic resonance imaging showed bilateral hyperintensity corresponding to the anterior horns of grey matter in the conus.
Keywords: Spinal cord infarction; myelopathy; magnetic resonance imaging